2017
DOI: 10.1515/jcbtp-2017-0013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Results of Online and Offline Customer Satisfaction & Loyalty Surveys in Banking Services in Montenegro

Abstract: Abstract:The logic that customer satisfaction is the starting point of marketing and business activities is based on the assumption that customer satisfaction leads to customer loyalty, keeping in mind all of the positive effects that customer loyalty has on business success of an organization. Because of this, marketing and management theory and practice dedicate particular attention to the concepts of customer satisfaction and loyalty. In this paper we will use the surveys of customers of banking services no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The service quality concept is all encompassing, which covers both the outcomes of service and the execution process of services. According to Jovović et al (2017), Bourne (2016), Lehtinen, U. and Lehtinen, J. R. (1991), the evaluation of customer regarding the result of service process is the service outcome. However, the end product of the execution is transferred to the customer is known as the service delivery (Parasuraman et al 1988).…”
Section: Service Quality Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The service quality concept is all encompassing, which covers both the outcomes of service and the execution process of services. According to Jovović et al (2017), Bourne (2016), Lehtinen, U. and Lehtinen, J. R. (1991), the evaluation of customer regarding the result of service process is the service outcome. However, the end product of the execution is transferred to the customer is known as the service delivery (Parasuraman et al 1988).…”
Section: Service Quality Dimensionsmentioning
confidence: 99%
“…According to Parasuraman et al (1985Parasuraman et al ( , 1988, the reliability is the most pivotal component in conservative services, and includes the correct order execution in the true spirit of its placement, correct records; correct quote; accurate billing; results are more authenticated than directive; and provide the promised services. Reliability is also considered more vital factor for banking services (Jovović et al 2017;Yang et al 2004). Parasuraman et al (1985) in their research studied the SERVQUAL model by incorporating the data collected from four identified companies, which included banks, long distance phone companies, credit card companies, and company's maintenance services.…”
Section: Reliability As An Servqual Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Jovović et al (2017), who conducted research on the renewal of the electronic banking platform in a banking entity, a staged procedure that took into account user needs research, costs, design considerations, and performance testing was required for the electronic implementation. Consumers' willingness to utilize electronic banking as a result of this process led to an increase in the visualization of banking, indicating that users value innovation, renewal, and investment in electronic banking.…”
Section: Literature Reviewmentioning
confidence: 99%